Inhibition of Sphingosine Kinase 1 Attenuates Sepsis-induced Microvascular Leakage via Inhibiting Macrophage NLRP3 Inflammasome Activation in Mice. (June 2020) - Zhong, Ming; Wu, Wei; Wang, Yingqin; Mao, Hailei; Song, Jieqiong; Chen, Song; Zhu, Duming
Abstract : Background: Sepsis is the overwhelming inflammatory response to infection, in which nucleotide-binding oligomerization domain-like receptor containing pyrin domain 3 (NLRP3) inflammasome plays a crucial role. Shingosine-1-phosphate is reported to evoke NLRP3 inflammasome activation. Sphingosine kinase 1 (SphK1) is the major kinase that catalyzes bioactive lipid shingosine-1–phosphate formation and its role in sepsis remains uncertain. The authors hypothesize that SphK1 elicits NLRP3 inflammasome activation and exacerbates sepsis. Methods: Peripheral blood mononuclear cells were isolated from septic patients and healthy volunteers to measure messenger RNA (mRNA) expression. In mice, sepsis was induced by cecal ligation and puncture. Bone marrow–derived macrophages were prepared from C57BL/6J wild-type, Casp1 −/−, Nlrp3 −/− and SphK1 −/− mice. PF-543 was used as the specific inhibitor of SphK1. Mortality, peripheral perfusion, lung Evan's blue dye index, lung wet/dry ratio, lung injury score, lung myeloperoxidase activity, NLRP3 activation, and function of endothelial adherens junction were measured. Results: SphK1 mRNA expression was higher in cells from septic patients versus healthy volunteers (septic patients vs. healthy volunteers: 50.9 ± 57.0 fold change vs. 1.2 ± 0.1 fold change, P < 0.0001) and was positively correlated with IL-1β mRNA expression in these cells ( r = 0.537, P = 0.012) and negatively correlated with PaO2 /FIO2 ratios ( r = 0.516, P = 0.017). In mice that had undergone cecal ligation and puncture, the 5-day mortality was 30% in PF-543–treated group and 80% in control group (n = 10 per group, P = 0.028). Compared with controls, PF-543–treated mice demonstrated improved peripheral perfusion and alleviated extravascular Evan's blue dye effusion (control vs. PF-543: 25.5 ± 3.2 ng/g vs. 18.2 ± 1.4 ng/g, P < 0.001), lower lung wet/dry ratio (control vs. PF-543: 8.0 ± 0.2 vs. 7.1 ± 0.4, P < 0.0001), descending lung injury score, and weaker lung myeloperoxidase activity. Inhibition of SphK1 suppressed caspase-1 maturation and interleukin-1β release through repressing NLRP3 inflammasome activation, and subsequently stabilized vascular endothelial cadherin through suppressing interleukin-1β–evoked Src-mediated phosphorylation of vascular endothelial cadherin. Conclusions: SphK1 plays a crucial role in NLRP3 inflammasome activation and contributes to lung injury and mortality in mice polymicrobial sepsis. Abstract : In peripheral blood mononuclear cells from septic patients, lipopolysaccharide-stimulated sphingosine-1-phosphate messenger RNA expression was higher than in cells from healthy volunteers. In male mouse model of sepsis, treatment with a specific inhibitor of sphingosine kinase 1 decreased mortality, improved peripheral perfusion, and diminished capillary leak. Results suggest that sphingosine kinase 1 may participate in NLRP3 activation, and septic lung injury and mortality in mice.Supplemental Digital Content is available in the text.